Magnetic metal powder and manufacturing method thereof

By using the DC plasma method in the gas phase condensation device, magnetic metal powder with high density filling and excellent magnetic properties is generated, and the problem of difficult to produce high density filling and excellent magnetic properties in the prior art is solved, and efficient magnetic properties and filling density are achieved.

JP2025060427APending Publication Date: 2025-04-10MITSUI MINING & SMELTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024144992
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-08-26
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

It is difficult to produce a magnetic metal powder capable of high density filling and excellent magnetic properties.

Method used

By using the DC plasma method in the gas phase condensation device, magnetic metal powders with specific particle size distribution and high thermal stability are generated. The method includes introducing a matrix powder containing a magnetic metal element into the plasma curtain, condensing the gas phase to generate magnetic metal particles, and controlling the particle size and aggregation of the powder by adjusting the flow state of the plasma curtain and the gas phase condensation conditions.

Benefits of technology

Magnetic metal powders with high density filling and excellent magnetic properties are achieved, improving the performance and filling density of the inductor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060427000001_ABST
    Figure 2025060427000001_ABST
Patent Text Reader

Abstract

To provide a magnetic metal powder which can be packed at a high density and has good magnetic properties.SOLUTION: A magnetic metal powder includes a magnetic metal element. The magnetic metal powder has a mass increase of 6.0% or less when it reaches 600°C when heated from 25°C at a heating rate of 10°C / min under an air flow of 150 mL / min. The magnetic metal powder has a value of D50 / SSA, which is the ratio of the volume cumulative particle size D50 (μm) at 50% cumulative volume measured by a laser diffraction scattering particle size distribution measurement method to the BET specific surface area SSA (m2 / g), of 0.010 or more and 1.0 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetic metal powder and a method for producing the same. The present invention also relates to a magnetic paste, a dust core, and an inductor using the magnetic metal powder. [Background technology]

[0002] As small portable devices become more sophisticated and multifunctional, inductors that can handle large currents, i.e., power inductors, are required for use in such devices. In order to pass large currents through an inductor, it is advantageous to use a magnetic material with high saturation magnetic flux density (saturation magnetization) as the material that constitutes the inductor. While ferrite has traditionally been the main magnetic material used for inductors, in recent years, metallic materials with higher saturation magnetization have been attracting attention. When using metallic materials, core-shell particles with an insulating coating are required to reduce eddy current loss in the inductor.

[0003] As an example of the core-shell particles, Patent Document 1 discloses silicon oxide-coated iron powder in which the surfaces of iron particles having an average particle size of 0.25 μm or more and 0.80 μm or less and an average axial ratio of 1.5 or less are coated with silicon oxide. Patent Document 2 discloses a silicon oxide-coated soft magnetic powder in which the surface of a soft magnetic powder containing 20 mass % or more of iron is coated with silicon oxide. The applicant has also previously proposed a metal particle having a core portion containing a magnetic metal element and a shell portion disposed on the surface of the core portion and containing an oxide of silicon (see Patent Document 3). The coverage rate of the core portion by the shell portion of this metal particle is 70% or more, as measured by element mapping of the cross section of the particle. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-123933 A [Patent Document 2] JP 2019-143241 A [Patent Document 3] Patent Publication No. 2021-175827 Summary of the Invention [Problem to be solved by the invention]

[0005] At present, metal cores in which magnetic metal powder and a coil are integrally molded are increasingly being used as power inductors. When manufacturing a metal core, it is necessary to pack the magnetic metal powder at a high density. For this purpose, it is preferable that the magnetic metal powder has a small particle size and a nearly spherical shape. In addition, from the viewpoint of sufficiently progressing sintering to improve the magnetic properties, it is desirable that the magnetic metal powder has high heat resistance. Therefore, an object of the present invention is to provide a magnetic metal powder which can be packed at a high density and has good magnetic properties. [Means for solving the problem]

[0006] The present invention provides a magnetic metal powder containing a magnetic metal element, When the temperature is increased from 25°C at a rate of 10°C / min under an air flow of 150 mL / min and the temperature reaches 600°C, the mass increase is 6.0% by mass or less; BET specific surface area SSA(m 2 / g) at 50% cumulative volume by the laser diffraction scattering particle size distribution measurement method 50 (μm) ratio D 50 The present invention provides a magnetic metal powder having a / SSA value of 0.010 or more and 1.0 or less.

[0007] The present invention also provides a magnetic metal powder containing a magnetic metal element, When the temperature is increased from 25°C at a rate of 10°C / min under an air flow of 150 mL / min and the temperature reaches 600°C, the mass increase is 1.5% by mass or less; BET specific surface area SSA(m2 / g) at 50% cumulative volume by the laser diffraction scattering particle size distribution measurement method 50 (μm) ratio D 50 The present invention provides a magnetic metal powder having a / SSA value of 10 or more and 100 or less.

[0008] The present invention further provides a method for producing a magnetic metal powder, comprising the steps of supplying first mother powder containing a magnetic metal element into a plasma flame in a laminar flow state generated in a chamber, gasifying the mother powder in the plasma flame, and cooling the gasified mother powder to generate magnetic metal particles, The present invention provides a method for producing magnetic metal powder, which maintains the laminar flow state of the plasma flame for a length of 1.0 cm to 20 cm. Effect of the Invention

[0009] According to the present invention, there is provided a magnetic metal powder which can be packed at a high density and has good magnetic properties. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic diagram showing an example of a DC plasma device for producing the magnetic metal powder of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described below based on its preferred embodiments. The magnetic metal powder of the present invention is composed of an aggregate of magnetic metal particles. The magnetic metal particles contain a magnetic metal element. The magnetic metal particles may be composed of a single magnetic metal element, may be composed of an alloy of two or more magnetic metal elements, or may be composed of an alloy of one or more magnetic metal elements and one or more non-magnetic metal elements. The magnetism referred to in the present invention means ferromagnetism. Therefore, the magnetic metal element used in the present invention has ferromagnetism. In the present invention, it is preferable to use at least one element selected from iron (Fe), cobalt (Co), and nickel (Ni) as the metal element having ferromagnetism from the viewpoint of increasing the saturation magnetic flux density and from the viewpoint of economy. Among these, for example, when Fe element is used, not only single Fe but also alloys using Fe element such as FeSi alloys (including FeSi, FeSiCr, FeSiAl, and FeSiB), FeNi alloys (including FeNi, FeNiMo, FeNiCr, FeNiCu, and FeNiNb), FeCo alloys (including FeCo, FeCoV, and FeCoNi), and FeCr alloys (including FeCr and FeCrSi) are preferably used.

[0012] The magnetic metal powder of the present invention preferably has little aggregation between primary particles. When the magnetic metal powder of the present invention is used as a material for a power inductor, for example, the fact that there is little aggregation between primary particles is advantageous from the viewpoint of improving the dispersibility and packing property of the particles and improving the performance of the power inductor. The degree of particle aggregation can be measured, for example, by the BET specific surface area (SSA) (m 2 / g) at 50% cumulative volume by the laser diffraction scattering particle size distribution measurement method 50 (μm) ratio D 50 It can be evaluated using the / SSA value. In the magnetic metal powder of the present invention, D 50 From the viewpoint of improving the dispersibility of the particles, the value of / SSA is preferably 1.0 or less, more preferably 0.50 or less, and even more preferably 0.25 or less. From a similar perspective, D 50The value of / SSA is preferably 0.010 or more, more preferably 0.050 or more, and even more preferably 0.10 or more. In this specification, a primary particle refers to an object that can be recognized as the smallest unit of a particle, judging from its apparent geometric shape.

[0013] The BET specific surface area of ​​the magnetic metal powder of the present invention is measured by the following method. The adsorption gas is 30% by volume of nitrogen gas, and the carrier gas is 70% by volume of helium gas mixed with nitrogen and helium. The BET specific surface area measuring device is Mountec Co., Ltd.'s HM model-1210. Measurements are performed according to "(3.5) One-point method" in "6.2 Flow method" of JIS R1626 "Gas adsorption of fine ceramic powders - Measurement method of specific surface area by BET method".

[0014] Regarding the degree of aggregation of primary particles, the magnetic metal powder of the present invention has a volume cumulative particle size D at 50% of the cumulative volume measured by scanning electron microscope observation. SEM50 D 50 D is the ratio of 50 / D SEM50 It is also preferable that the value of D is in a specific range. SEM50 represents the particle size of the primary particle, and D 50 represents the particle size of secondary particles, which are aggregates of multiple primary particles, and D 50 / D SEM50 The value of is a measure of the degree of aggregation between particles, i.e., the proportion of primary particles. In the magnetic metal powder of the present invention, D 50 / D SEM50 is preferably 2.8 or less, more preferably 2.0 or less, and even more preferably 1.5 or less, whereby the magnetic metal powder of the present invention has good packing properties and makes it easy to increase the saturation magnetic flux density. D 50 / D SEM50 Theoretically, the lower limit is 1.0, but 1.1 is more realistic.

[0015] From the viewpoint of suppressing aggregation between primary particles and enhancing packing properties, it is preferable that the magnetic metal powder of the present invention contains as few fine particles as possible. From this viewpoint, the magnetic metal powder of the present invention has an SSA value of 5.0m 2 / g or less, and 4.8m 2 More preferably, it is 4.5m / g or less. 2 In addition, when the magnetic metal powder of the present invention is used as a material for a power inductor, for example, from the viewpoint of making it difficult for eddy currents to occur, the SSA value of the magnetic metal powder of the present invention is preferably 1.5 m 2 / g or more, and 2.0m 2 More preferably, it is 2.4m / g or more. 2 It is more preferable that the molecular weight is 1 / g or more.

[0016] As with the above-mentioned SSA, from the viewpoint of suppressing aggregation between primary particles and enhancing packing properties, the magnetic metal powder of the present invention has its D SEM50 The value of D is preferably 0.15 μm or more, more preferably 0.20 μm or more, and even more preferably 0.25 μm or more. Furthermore, when the magnetic metal powder of the present invention is used as a material for a power inductor, for example, from the viewpoint of making it difficult for eddy currents to occur, the D SEM50 The value is preferably 0.90 μm or less, more preferably 0.75 μm or less, and even more preferably 0.65 μm or less.

[0017] The above mentioned D SEM50 Similarly, from the viewpoint of suppressing aggregation between primary particles and enhancing packing property, the magnetic metal powder of the present invention has its D 50 The magnetic metal powder of the present invention has a value of preferably 0.30 μm or more, more preferably 0.35 μm or more, and even more preferably 0.40 μm or more. In addition, when the magnetic metal powder of the present invention is used as a material for a power inductor, for example, from the viewpoint of making it difficult for an eddy current to occur, its D 50 The value is preferably 1.1 μm or less, more preferably 0.95 μm or less, and even more preferably 0.90 μm or less.

[0018] D 50 In relation to the above, the volume cumulative particle size D at 90% cumulative volume measured by the laser diffraction scattering particle size distribution measurement method is 90 The value of D is set so that the magnetic metal powder of the present invention is less likely to generate eddy currents when used as a material for a power inductor, for example. 50 Provided that the thickness is greater than 1.0 μm, the thickness is preferably 5.0 μm or less, more preferably 4.0 μm or less, and even more preferably 3.5 μm or less. 90 The value of D is set to improve the packing property of the powder. 50 provided that the thickness is greater than 1.0 μm, preferably 1.0 μm or more, more preferably 1.2 μm or more, and even more preferably 1.4 μm or more.

[0019] Similarly, D 50 In relation to the above, the magnetic metal powder of the present invention has a volume cumulative particle size D at 10% by volume cumulative volume measured by a laser diffraction scattering type particle size distribution measurement method. 10 From the viewpoint of suppressing aggregation between primary particles and improving packing properties, the value of D 50 Provided that the thickness is smaller than 0.15 μm, the thickness is preferably 0.15 μm or more, more preferably 0.18 μm or more, and even more preferably 0.20 μm or more. 10 The value of D is set to improve the packing property of the powder. 50 Provided that the thickness is smaller than 0.35 μm, it is preferably 0.30 μm or less, and more preferably 0.28 μm or less.

[0020] In the present invention, D 10 , D 50 and D. 90 The measurement can be carried out, for example, by the following method. That is, 0.1 g of the measurement sample is mixed with 50 mL of water and dispersed for 1 minute using an ultrasonic homogenizer (US-300T, manufactured by Nippon Seiki Seisakusho Co., Ltd.). Then, the particle size distribution is measured using a laser diffraction scattering type particle size distribution measuring device, such as MT3300 EXII manufactured by Microtrack Bell.

[0021] On the other hand, D SEM50 is defined as the volume cumulative particle diameter at 50% of the cumulative volume of the volume calculated by randomly selecting 1,000 particles from a scanning electron microscope image of magnetic metal particles that are not overlapping, measuring the particle diameter (Heywood diameter), and then calculating the volume of the particles assuming that they are spherical from the obtained particle diameter.

[0022] As mentioned above, it is preferable that the magnetic metal powder of the present invention contains as few fine particles as possible. This means that the magnetic metal powder of the present invention has a large crystallite size. Specifically, the magnetic metal powder of the present invention preferably has a crystallite size of 50 nm or more and 130 nm or less, more preferably 50 nm or more and 110 nm or less, and even more preferably 50 nm or more and 95 nm or less. Magnetic metal particles with such a large crystallite size are preferable because they have a high purity due to the small number of grain boundaries, and therefore have an improved saturation magnetic flux density. Magnetic metal particles with a crystallite size in this range can be suitably manufactured, for example, by the manufacturing method described below.

[0023] The method for measuring the crystallite size varies depending on the type of magnetic metal particle, but in general, it is calculated from the peak width (half width) of the X-ray diffraction peak in the crystal plane with the highest intensity within the measurement range (20° to 150°) using the Scherrer formula below. For example, when an FeCo alloy is used as the magnetic metal particle, the crystallite size is calculated from the peak width (half width) of the X-ray diffraction peak in the crystal plane with the highest intensity within the measurement range (2θ: 20° to 150°) using CuKα radiation, with a sampling width of 0.01° and a scan speed of 2° / min. <110> It is calculated from the peak width (half width) of the X-ray diffraction peak at Scherrer's formula: D=Kλ / βcosθ D: Crystallite size (unit: nm) K: Scherrer constant (0.9400) λ: wavelength of X-rays (unit: Kα1 1.54056Å) β: Half-width (unit: rad) θ: Diffraction angle (unit: rad)

[0024] The shape of the magnetic metal particles of the present invention is not particularly limited, and various shapes such as spherical, flake, polyhedral, etc. can be adopted. From the viewpoint of increasing the packing property of the magnetic metal particles and increasing the saturation magnetic flux density, the shape of the magnetic metal particles is preferably spherical. The spherical shape means that the circularity coefficient measured by the following method is preferably 0.85 or more, more preferably 0.90 or more. The circularity coefficient is calculated as follows. A scanning electron microscope image of a magnetic metal particle is taken, and 1000 particles that do not overlap are randomly selected. When the area of ​​the two-dimensional projection image of the particle is S and the perimeter is L, the circularity coefficient of the particle is 4πS / L. 2 The circularity coefficient is calculated from the formula. The arithmetic average of the circularity coefficients of each particle is the circularity coefficient mentioned above. When the two-dimensional projected image of a particle is a perfect circle, the circularity coefficient of the particle is 1.

[0025] The magnetic metal powder of the present invention may further contain a non-magnetic metal element in addition to containing a magnetic metal element. In particular, it is advantageous from the viewpoint of reducing eddy current loss due to improved electrical insulation that the non-magnetic metal element is contained in the shell portion arranged on the outermost surface of the core portion containing the magnetic metal element. In particular, it is preferable from the viewpoint of further reducing eddy current loss that the metal particles constituting the magnetic metal powder of the present invention have a core portion containing a magnetic metal element and a shell portion arranged on the surface of the core portion and containing an oxide of a non-magnetic metal element. This shell portion containing an oxide of a non-magnetic metal element acts as an electrical insulating layer for the core portion, which further reduces eddy current loss. The shell portion may be crystalline or amorphous as long as it has electrical insulation.

[0026] The non-magnetic metal element is preferably at least one of Mg, Al, Si, Ca, Zr, Ti, Hf, Zn, Mn, rare earth elements (excluding those having magnetism), Ba and Sr from the viewpoint of improving the electrical insulation of the shell part, and is more preferably any of Al, Si and Zr. These non-magnetic metal elements may be used alone or in combination of two or more. In particular, it is preferable that alumina, which is an oxide of Al, or silica, which is an oxide of Si, is present on the outermost surface from the viewpoint of further improving the electrical insulation. In this case, the magnetic metal powder has a powder resistance of 1.0×10 when compressed at 20 kN. 7 It is preferable for the material to exhibit high insulation properties of Ω·cm or more.

[0027] In particular, when manufacturing metal particles having a core portion and a shell portion by the method described below, it is preferable, from the standpoint of ease of manufacturing, to use a non-magnetic metal element constituting the shell portion whose oxide has a boiling point lower than the boiling point of the metal constituting the core portion.

[0028] The core may be composed of only magnetic metal elements or may be formed of an alloy containing both magnetic and non-magnetic metal elements, while the shell is preferably composed of only oxides of non-magnetic metal elements and does not contain magnetic metal elements.

[0029] From the viewpoint of electrical insulation, it is preferable that the shell part of the metal particle having the core part and the shell part uniformly covers the entire area of ​​the core part. However, on the other hand, an increase in the amount of the shell part covered leads to a decrease in the magnetic force of the metal particle as a whole. Taking these matters into consideration, the ratio of the shell part to the entire metal particle is preferably 1.0 mass% or more and 5.0 mass% or less, more preferably 1.0 mass% or more and 4.0 mass% or less, and even more preferably 1.0 mass% or more and 3.0 mass% or less. By setting the content ratio as such, it is also possible to easily obtain the desired particle size distribution as referred to in the present invention. For example, when the shell part is made of SiO2, the ratio of the shell part to the metal particle can be measured by converting the Si concentration obtained by ICP analysis into the SiO2 concentration. When the shell part is made of another material, it can be measured in the same manner.

[0030] If the shell is too thick, the particles are likely to aggregate and affect the packing properties, so it is desirable that the shell thickness is as small as possible. On the other hand, if the shell is too thin, the effect of electrical insulation by the shell is less likely to be realized, and eddy current loss tends to increase. Therefore, from the viewpoint of balancing the two, it is preferable to form a shell having a thin and dense structure. Making the shell have a dense structure contributes to improving the heat resistance of the magnetic metal powder of the present invention. The heat resistance of the magnetic metal powder of the present invention can be evaluated by the resistance of the particles to oxidation. In detail, the mass increase ΔW when the temperature is raised from 25° C. to 600° C. at a heating rate of 10° C. / min under air flow of 150 mL / min is 600 is preferably 6.0% by mass or less, more preferably 5.5% by mass or less, and even more preferably 4.5% by mass or less. 600 There is no particular limit to the lower limit of , and the closer to zero the better. 600 The value of is obtained by thermogravimetry.

[0031] The heat resistance of the magnetic metal powder of the present invention is ΔW 600The mass increase ΔW when the temperature is raised from 25°C to 700°C under the same conditions 700 , and the mass increase ΔW when the temperature is raised from 25°C to 800°C 800 The magnetic metal powder of the present invention can also be evaluated by ΔW 700 is preferably 12 mass% or less, more preferably 8.0 mass% or less, and even more preferably 6.0 mass% or less. 800 is preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 10% by mass or less.

[0032] As long as the shell has the above-mentioned heat resistance, it is desirable that the thickness of the shell is small. Specifically, regardless of whether the shell covers the entire surface of the core, the thickness of the shell is preferably 0.5 nm to 50 nm, more preferably 0.5 nm to 30 nm, and even more preferably 1.0 nm to 10 nm. The thickness of the shell is determined by identifying the shell by cross-sectional observation using a transmission electron microscope (TEM) and measurement using energy dispersive X-ray analysis (EDS) and measuring the thickness.

[0033] According to the present invention, magnetic metal particles and magnetic metal powders other than the above-mentioned magnetic metal particles and magnetic metal powders are also provided. The other magnetic metal particles and magnetic metal powders are distinguished by having a larger particle size than the above-mentioned magnetic metal particles and magnetic metal powders. In this sense, in the following description, the other magnetic metal particles and magnetic metal powders are also referred to as "coarse magnetic metal particles" and "coarse magnetic metal powders", respectively. The above-mentioned magnetic metal particles and magnetic metal powders are also referred to as "fine magnetic metal particles" and "fine magnetic metal powders". In addition, "coarse magnetic metal particles" and "fine magnetic metal particles" are also collectively referred to simply as "magnetic metal particles", and "coarse magnetic metal powders" and "fine magnetic metal powders" are also collectively referred to simply as "magnetic metal powders". The effect of the present invention, that the coarse magnetic metal particles and coarse magnetic metal powders can also be densely packed and have good magnetic properties, is achieved.

[0034] The coarse magnetic metal particles and magnetic metal powder will be described below. The above explanations regarding the fine magnetic metal particles and magnetic metal powder apply to points not specifically described regarding the coarse magnetic metal particles and magnetic metal powder. Coarse magnetic metal powder has the following characteristics: 50 The value of D of fine magnetic metal powder 50 It is preferable that the thickness is 5.0 μm or more, more preferably 5.5 μm or more, and even more preferably 5.9 μm or more, provided that the thickness is greater than 5.0 μm. 50 The value of is preferably less than 18 μm, more preferably 15 μm or less, and even more preferably 13 μm or less. By having such a particle size and a mass increase, which will be described later, being equal to or less than a specific value, it is possible to obtain a magnetic metal powder that can be packed at a high density and has good magnetic properties.

[0035] Coarse magnetic metal powder has the following characteristics: 90 The value of D 50 It is preferable that the thickness is 10 μm or more, more preferably 11 μm or more, and even more preferably 13 μm or more, provided that the thickness is greater than 10 μm. 90 The value of D 50 provided that the thickness is greater than 30 μm, preferably 24 μm or less, and more preferably 22 μm or less.

[0036] Coarse magnetic metal powder has the following characteristics: 10 The value of D 50 Provided that the thickness is smaller than D, it is preferably 2.0 μm or more, more preferably 2.5 μm or more, and even more preferably 3.0 μm or more. 10 The value of D 50 With the condition that it is smaller than 7.5 μm, it is preferably less than 6.5 μm, and more preferably 6.0 μm or less.

[0037] The above-mentioned coarse magnetic metal powder D 50In relation to the D SEM50 The value of D of fine magnetic metal powder SEM50 It is preferable that the thickness is 5.0 μm or more, more preferably 5.5 μm or more, and even more preferably 6.0 μm or more, provided that the thickness is greater than 5.0 μm. SEM50 The value of D of the coarse-grained magnetic metal powder is preferably 18 μm or less, more preferably 15 μm or less, and even more preferably 13 μm or less. SEM50 It is preferable that has such a value.

[0038] In coarse magnetic metal powder, D 50 The value of / SSA is preferably 100 or less, more preferably 80 or less, and even more preferably 65 or less. Also, D 50 The value of / SSA is preferably 10 or more, more preferably 11 or more, and even more preferably 13 or more.

[0039] In coarse magnetic metal powder, D 50 / D SEM50 is preferably 2.5 or less, more preferably 2.0 or less, even more preferably 1.5 or less, and even more preferably 1.20 or less. This allows the magnetic metal powder of the present invention to have good packing properties and to easily increase the saturation magnetic flux density. D 50 / D SEM50 Theoretically, the lower limit of is 1.0.

[0040] Coarse magnetic metal powder has an SSA value of 0.10m 2 / g or more, and 0.12m 2 More preferably, it is 0.14 m 2 It is more preferable that the coarse-grained magnetic metal powder has an SSA value of 0.50m 2 / g or less, and 0.40m 2 More preferably, it is 0.25m / g or less. 2It is even more preferable that the molecular weight is not more than 1 / g.

[0041] The coarse magnetic metal powder preferably has a crystallite size of 60 nm to 130 nm, more preferably 65 nm to 120 nm, and even more preferably 70 nm to 110 nm. Magnetic metal particles with such a large crystallite size have fewer grain boundaries, resulting in higher purity and improved saturation magnetic flux density, making them preferable. Magnetic metal particles with a crystallite size in this range can be suitably manufactured, for example, by the manufacturing method described below.

[0042] From the viewpoint of improving heat resistance, the coarse magnetic metal powder has a mass increase of ΔW 600 is preferably 1.5% by mass or less, more preferably 1.4% by mass or less, even more preferably 1.1% by mass or less, and even more preferably 0.7% by mass or less. 600 There is no particular restriction on the lower limit value, and the closer to zero it is, the more preferable.

[0043] The heat resistance of coarse magnetic metal powder is ΔW 600 The mass increase ΔW when the temperature is raised from 25°C to 700°C under the same conditions 700 , and the mass increase ΔW when the temperature is raised from 25°C to 800°C 800 It can also be evaluated by ΔW of coarse magnetic metal powder. 700 is preferably 3.0 mass% or less, more preferably 2.0 mass% or less, even more preferably 1.5 mass% or less, and even more preferably 0.9 mass% or less. In addition, ΔW 800 is preferably 3.8 mass % or less, more preferably 3.0 mass % or less, even more preferably 2.5 mass % or less, and even more preferably 1.6 mass % or less.

[0044] Next, a preferred manufacturing method of the magnetic metal particles of the present invention will be described. First, a manufacturing method of fine magnetic metal particles will be described. In this manufacturing method, mother powder containing a magnetic metal element is subjected to a direct current thermal plasma (hereinafter also referred to as "DC plasma") method to generate fine magnetic metal particles from the mother powder. In detail, this manufacturing method has a step of supplying the mother powder to a plasma flame in a laminar flow state generated in a chamber, gasifying the mother powder, and cooling the gasified mother powder to generate fine magnetic metal particles. When the fine magnetic metal particles are composed of a single magnetic metal element, the mother powder may be made of the single magnetic metal element. When the fine magnetic metal particles are composed of an alloy of two or more magnetic metal elements, the mother powder may be made of the alloy. For example, when the target fine magnetic metal particles are composed of an FeCo alloy, the mother powder made of an FeCo alloy may be used. There is no particular limitation on the manufacturing method of the mother powder, and for example, atomized powder, wet reduced powder, electrolytic powder, etc. may be used.

[0045] FIG. 1 shows a DC plasma device suitable for use in this manufacturing method. As shown in the figure, the DC plasma device 1 includes a powder supply device 2, a chamber 3, a DC plasma torch 4, a collection pot 5, a powder supply nozzle 6, a gas supply device 7, and a pressure adjustment device 8. In addition, in the DC plasma device 1, a cylindrical body 9 surrounding the plasma flame is arranged in the chamber 3 and directly below the plasma torch 4. The cylindrical body 9 has a longitudinal direction and a width direction perpendicular to the longitudinal direction. The inside of the cylindrical body 9 is hollow. The outer peripheral surface of the cylindrical body 9 and the inner wall of the chamber 3 are connected by a partition plate 10. The partition plate 10 is located below the lower end of the plasma torch 4 and extends radially in the horizontal direction from the outer surface of the cylindrical body 9. Therefore, the inside of the chamber 3 is divided into an upper part and a lower part with the partition plate 10 as a boundary. In this device, the mother powder passes through the inside of the plasma torch 4 from the powder supply device 2 through the powder supply nozzle 6. A gas for generating thermal plasma (hereinafter also referred to as "plasma gas") is supplied from a gas supply device 7 to the plasma torch 4 to generate a plasma flame. The mother powder is gasified in the plasma flame generated by the plasma torch 4 and released into the chamber 3. The gasified mother powder is then cooled and becomes fine particles of fine magnetic metal particles 11, which are accumulated and collected in the collection pot 5.

[0046] From the viewpoint of supplying sufficient energy to the base powder in the plasma flame to successfully form submicron-order fine particles, it is preferable to adjust the plasma flame so that it is thick and long in a laminar flow state. Whether the plasma flame is in a laminar flow state can be determined by whether the aspect ratio of the frame length to the frame width (hereinafter, frame aspect ratio) is 3 or more when the plasma flame is observed from the side where the frame width is observed to be the widest. Specifically, if the frame aspect ratio is 3 or more, it can be determined to be in a laminar flow state, and if it is less than 3, it can be determined to be in a turbulent flow state.

[0047] In particular, from the viewpoint of suppressing aggregation of the fine magnetic metal particles, it is preferable to adjust the length of the plasma flame so that it is in a laminar state. Specifically, it is preferable to maintain the laminar state of the plasma flame for 1.0 cm or more, more preferably for 2.0 cm or more, and even more preferably for 4.0 cm or more. It is also preferable to maintain the laminar state for 20 cm or less, more preferably for 15 cm or less, and even more preferably for 12 cm or less. By maintaining the laminar state of the plasma flame for 20 cm or more, the temperature of the plasma flame is less likely to drop and is more likely to be uniform, so that the generation of the fine magnetic metal particles is promoted. Furthermore, the generated magnetic metal particles are less likely to return, and the magnetic metal particles are less likely to become coarse due to collisions between the particles. Furthermore, by maintaining the laminar state of the plasma flame for 15 cm or less, the effect of making the temperature of the plasma flame more uniform is achieved. The return of the generated fine magnetic metal particles is further suppressed by the partition plate 10 dividing the chamber 3 into upper and lower spaces.

[0048] In order to make the plasma flame thick and long in a laminar flow state, it is advantageous to adjust the plasma output and plasma gas flow rate. In detail, the plasma output of the DC plasma device is preferably 2.0 kW or more and 100 kW or less, more preferably 2.0 kW or more and 40 kW or less, and even more preferably 2.0 kW or more and 20 kW or less. The gas flow rate of the plasma gas is preferably 0.10 L / min or more and 25 L / min or less, and more preferably 0.50 L / min or more and 21 L / min or less. As the plasma gas, reducing gas such as hydrogen gas, and inert gas such as nitrogen gas and argon gas are preferable.

[0049] From the viewpoint of supplying sufficient thermal energy to the base powder in the plasma flame to successfully form fine particles on the submicron order, as well as to prevent coarse base powder from remaining, the ratio of plasma output to the amount of base powder supplied is preferably 0.003 kW·min / g or more and 20 kW·min / g or less, and more preferably 0.050 kW·min / g or more and 15 kW·min / g or less.

[0050] From the viewpoint of reliably obtaining the flow rate required for gasifying the base powder while stably maintaining the plasma flame in a laminar flow state, the ratio of the plasma gas flow rate to the plasma output (unit: L / (min kW)) is set to preferably 0.15 or more and 2.0 or less, more preferably 0.40 or more and 1.7 or less, and even more preferably 0.60 or more and 1.5 or less, while maintaining the plasma output and gas flow rate within the above-mentioned ranges.

[0051] In particular, in this manufacturing method, as shown in FIG. 1, a plasma flame is generated in a state where a cylindrical body 9 surrounding the plasma flame is placed directly below a plasma torch 4. The cylindrical body 9 refers to a portion different from the plasma torch 4 that generates the plasma. In this manufacturing method, it is preferable that at least a portion of the plasma flame is generated within the cylindrical body 9. The cylindrical body 9 suppresses a decrease in temperature of the plasma flame, thereby promoting grain growth, and thus fine magnetic metal particles having a desired particle size distribution can be successfully obtained. In addition, fine magnetic metal particles having a desired crystallite size can be successfully obtained.

[0052] There is no particular limitation on the cross-sectional shape of the cylindrical body 9. For example, the cross section may be a polygon such as a circle or a rectangle. From the viewpoint of effectively suppressing a temperature drop of the plasma flame, it is preferable that the cylindrical body 9 is a cylinder. In this case, from the viewpoint of effectively suppressing a temperature drop of the plasma flame, it is preferable that the center position of the cross section of the cylinder and the generation position of the plasma flame roughly coincide with each other. From the viewpoint of temperature durability against the plasma flame, preferred materials for the cylindrical body 9 include zirconia, carbon, alumina, quartz, silicon carbide, and the like.

[0053] It is preferable that the laminar flow state of the plasma flame described above occurs inside the cylindrical body 9 in order to further suppress the temperature drop of the plasma flame. In order to make this advantage more prominent, the vertical length of the portion of the plasma flame in the laminar flow state is set to a length L P The length of the cylindrical body 9 is L S Then, L S L for P The ratio of L P / L S The value is preferably 0.10 or more and 0.95 or less, more preferably 0.15 or more and 0.90 or less, and even more preferably 0.20 or more and 0.85 or less.

[0054] From the same viewpoint, when the cylindrical body 9 is a cylinder, it is preferable to maintain the laminar flow state of the plasma flame while maintaining the value of d / D at 0.003 or more, particularly 0.005 or more, and especially 0.010 or more, where D (mm) is the inner diameter of the cylinder and d (mm) is the maximum diameter of the plasma flame generated in the cylinder, because this suppresses heat dissipation and makes it easier to obtain metal particles with a uniform particle size. From this viewpoint, the closer the value of d / D is to 1, the more preferable it is. However, if the value of d / D is 1, it affects the stability of the plasma flame, so the value of d / D is preferably 0.20 or less, more preferably 0.15 or less, and even more preferably 0.10 or less.

[0055] When obtaining fine magnetic metal particles by the DC plasma method, the inventors have found through their research that it is easier to obtain fine magnetic metal particles with high heat resistance while suppressing the generation of fine powder by making the chamber in a low vacuum state rather than a high vacuum state. Specifically, the pressure in the chamber is preferably set to -0.01 kPa or more and -90 kPa or less, more preferably -0.50 kPa or more and -60 kPa or less, and even more preferably -1.0 kPa or more and -25 kPa or less, expressed as a gauge pressure.

[0056] When producing fine magnetic metal particles having a core and an electrically insulating shell using the DC plasma device 1 shown in Fig. 1, a mixture of a first mother powder containing a magnetic metal element and a second mother powder made of an oxide of a non-magnetic metal element, such as alumina or silica, may be used as the mother powder. By gasifying both mother powders in a plasma flame and cooling the gasified mother powders, fine magnetic metal particles can be produced that have a core containing a magnetic metal element and a shell that is disposed on the surface of the core and contains an oxide of a non-magnetic metal element, such as aluminum or silicon. In this case, it is advantageous to use a first mother powder whose boiling point is higher than that of the second mother powder. By using a mixed mother powder consisting of the first and second mother powders having such a temperature relationship, in the particle generation process, first, the evaporated and vaporized first mother powder is cooled, causing nucleation, aggregation, and condensation of the core part, forming the core part. Next, the evaporated and vaporized second mother powder (the second mother powder has a lower boiling point than the first mother powder) is cooled, causing nucleation, aggregation, and condensation on the surface of the core part, forming the shell part.

[0057] In particular, when the first and second mother powders are used to obtain fine magnetic metal particles having a core and a shell, it is preferable to generate a plasma flame in the above-mentioned cylindrical body 9 and set the dimensional relationship between the cylindrical body 9 and the plasma flame within the above-mentioned range. This suppresses the temperature drop of the plasma flame and makes the core densely covered by the shell. As a result, fine magnetic metal particles having a uniform particle size and improved heat resistance are obtained.

[0058] When obtaining fine magnetic metal particles having a core portion and a shell portion, the particle diameter D of the mother powder is set to 100 nm from the viewpoint of plasma sprayability of the mother powder and cost. 50 In both the first mother powder and the second mother powder, the D of the mother powder is preferably 3.0 μm or more and 50 μm or less, and more preferably 5.0 μm or more and 30 μm or less. 50 The measurement of D of metal particles mentioned above 50 This can be done in a similar manner to the measurement of

[0059] From the viewpoint of the production efficiency of the obtained fine magnetic metal particles, the supply rate of the mother powder is preferably 5 g / min to 200 g / min, more preferably 5 g / min to 100 g / min, and even more preferably 5 g / min to 60 g / min, expressed as the total amount of the first mother powder and the second mother powder. In addition, with regard to the ratio of the first mother powder to the second mother powder, it is preferable that the second mother powder is contained in an amount of 1 to 5 mass% in the total amount of the first mother powder and the second mother powder.

[0060] The shape of the mother powder is not particularly limited in either the first mother powder or the second mother powder, and examples thereof include dendritic, rod-like, flake-like, cubic, spherical, etc. From the viewpoint of stabilizing the supply efficiency to the plasma torch, it is preferable to use spherical mother powder.

[0061] In the preferred manufacturing method of the fine magnetic metal particles of the present invention, it is preferable to use SiO rather than SiO2 to form the shell portion made of an oxide of silicon. The reason is as follows. In the above-mentioned DC plasma method, the second mother powder is evaporated and then cooled to cause nucleation, aggregation, and condensation. When comparing SiO2 and SiO with respect to the boiling point and melting point, which are physical property values ​​related to this process, the melting point of SiO2 is 1650°C and the boiling point is 2230°C, while the melting point of SiO is 1702°C and the boiling point is 1880°C. Therefore, the temperature range in which SiO2 can maintain a liquid phase state is 580°C (=2230°C-1650°C), while the temperature range in which SiO2 can maintain a liquid phase state is 172°C (=1880°C-1702°C). In other words, the temperature range in which SiO can maintain a liquid phase state is narrower than that of SiO2. This means that the possibility of aggregation occurring due to surface tension in a liquid phase state is lower for SiO than for SiO2. The fact that aggregation caused by surface tension is unlikely to occur is advantageous in that it is possible to increase the coverage rate of the core part by the shell part and to prevent aggregation due to necking between particles. For these reasons, SiO is more preferable than SiO2 as the second mother powder for forming the shell part containing an oxide of silicon.

[0062] When SiO2 is used as the second mother powder, a shell part made of SiO2 is generally formed. On the other hand, when SiO2 is used as the second mother powder, SiO X (x is a number greater than 0 and equal to or less than 2). The value of x depends on the oxygen concentration in the chamber in the above-mentioned production method, etc.

[0063] The fine magnetic metal particles thus obtained tend to be spherical in shape. The fine magnetic metal particles are preferably used as a raw material for a sintered body as a fine magnetic metal powder, which is an aggregate of the fine magnetic metal particles. The sintered body is preferably used, for example, as a core material for a power inductor. In this case, from the viewpoint of reducing eddy current loss, it is advantageous for the fine magnetic metal particles to be composed of a core portion and an electrically insulating shell portion. On the other hand, the fine magnetic metal powder as an aggregate of the fine magnetic metal particles can be used in the form of a magnetic paste by adding a binder or a vehicle. The fine magnetic metal powder or magnetic paste described above can also be compressed and molded to form a dust core. Furthermore, the paste can be molded into a predetermined shape, dried, and solidified to form a solidified molded body, which can be used as a core material for a power inductor.

[0064] Next, a preferred method for producing the coarse magnetic metal particles will be described. For points not described regarding the method for producing the coarse magnetic metal particles, the above description regarding the method for producing the fine magnetic metal particles is applied. As described above, fine magnetic metal particles are produced by the crystal nucleation and crystal growth after the mother powder is gasified, whereas coarse magnetic metal particles are produced by lowering the plasma output, without the mother powder being gasified, and by heating the plasma to make the outer shape of the mother powder spherical. As a result, the particle size of the coarse magnetic metal particles is larger than that of the fine magnetic metal particles.

[0065] When producing coarse magnetic metal particles, it is preferable to set the plasma output of the DC plasma device lower than that when producing fine magnetic metal particles, in order to prevent the base powder from being gasified. Specifically, it is preferable to set the plasma output of the DC plasma device to 2.0 kW or more and 20 kW or less, more preferably to 3.0 kW or more and 18 kW or less, and even more preferably to 4.0 kW or more and 15 kW or less. The pressure inside the chamber is preferably set to a gauge pressure of -0.01 kPa or more and -90 kPa or less, more preferably -0.50 kPa or more and -60 kPa or less, and even more preferably -1.0 kPa or more and -25 kPa or less.

[0066] In relation to the above-described embodiment, the present invention further discloses the following magnetic metal powder, a magnetic paste, a dust core, and an inductor each containing the magnetic metal powder, and a method for producing the same.

[0067] [1] A magnetic metal powder containing a magnetic metal element, When the temperature is increased from 25°C at a rate of 10°C / min under an air flow of 150 mL / min and the temperature reaches 600°C, the mass increase is 6.0% by mass or less; BET specific surface area SSA(m 2 / g) at 50% cumulative volume by the laser diffraction scattering particle size distribution measurement method 50 (μm) ratio D 50 A magnetic metal powder having a / SSA value of 0.010 or more and 1.0 or less. [2] Volume cumulative particle size D at 50% cumulative volume observed by scanning electron microscope SEM50 (μm) vs. the volume cumulative particle size D 50 (μm) ratio D 50 / D SEM50 The magnetic metal powder according to [1], wherein the value is 1.0 or more and 2.8 or less. [3] The volume cumulative particle size D 50 The magnetic metal powder according to [1] or [2], wherein the particle size is 0.30 μm or more and 1.1 μm or less. [4] The BET specific surface area SSA is 1.5 m 2 / g or more 5.0m 2 / g or less. [5] Volume cumulative particle size D at 10% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 10 D 50 The magnetic metal powder according to any one of [1] to [4], having a particle size of 0.15 μm or more and 0.35 μm or less, with the condition that the particle size is smaller than 0.15 μm or less.

[0068] [6] Volume cumulative particle size D at 90% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 90 The magnetic metal powder according to any one of [1] to [5], having a particle size of 1.2 μm or more and 5.0 μm or less. [7] Alumina or silica is present on the outermost surface, The powder resistance when compressed with 20 kN is 1.0 x 10 7 The magnetic metal powder according to any one of [1] to [6], having a resistivity of Ω·cm or more. [8] The magnetic metal powder according to any one of [1] to [7], containing at least one of the magnetic metal elements selected from iron (Fe), cobalt (Co) and nickel (Ni). [9] The magnetic metal powder according to any one of [1] to [8], which contains FeSi or FeSiCr.

[10]

[11] A magnetic paste comprising the magnetic metal powder according to any one of [1] to [9]. A dust core comprising the magnetic metal powder according to any one of [1] to [9].

[12] An inductor comprising the magnetic metal powder according to any one of [1] to [9].

[0069]

[13] A method for producing a magnetic metal powder, comprising the steps of supplying a first mother powder containing a magnetic metal element into a plasma flame in a laminar flow state generated in a chamber, gasifying the mother powder in the plasma flame, and cooling the gasified mother powder to generate magnetic metal particles, A method for producing magnetic metal powder, in which the laminar flow state of the plasma flame is maintained for a length of 1.0 cm or more and 20 cm or less.

[14] The plasma flame is generated within a cylindrical body installed in the chamber; The manufacturing method described in

[13] , wherein the laminar flow state of the plasma flame is maintained while maintaining the value of d / D at 0.003 or more and 0.20 or less, where D (mm) is the inner diameter of the cylindrical body and d (mm) is the maximum diameter of the plasma flame.

[15] The manufacturing method according to

[13] or

[14] , wherein a second mother powder made of alumina or silica is supplied into the plasma frame together with the first mother powder, and both mother powders are gasified in the plasma frame, and the gasified mother powders are cooled to generate magnetic metal particles having a core portion containing the magnetic metal element and a shell portion disposed on the surface of the core portion and containing an oxide of aluminum or silicon.

[0070]

[16] A magnetic metal powder containing a magnetic metal element, When the temperature is increased from 25°C at a rate of 10°C / min under an air flow of 150 mL / min and the temperature reaches 600°C, the mass increase is 1.5% by mass or less; BET specific surface area SSA(m 2 / g) at 50% cumulative volume by the laser diffraction scattering particle size distribution measurement method 50 (μm) ratio D 50 A magnetic metal powder having a / SSA value of 10 or more and 100 or less.

[17] Volume cumulative particle size D at 50% cumulative volume observed by scanning electron microscope SEM50 (μm) vs. the volume cumulative particle size D 50 (μm) ratio D 50 / DSEM50 The magnetic metal powder according to

[16] , wherein the value is 1.0 or more and 2.5 or less.

[18] The volume cumulative particle size D 50 The magnetic metal powder according to

[16] or

[17] , wherein the particle size is 5.0 μm or more and less than 18 μm.

[19] The BET specific surface area SSA is 0.10 m 2 / g or more 0.50m 2 The magnetic metal powder according to any one of

[16] to

[18] , wherein the magnetic metal powder has a molecular weight of 1000 or less.

[20] Volume cumulative particle size D at 10% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 10 The magnetic metal powder according to any one of

[16] to

[19] , wherein the particle size is 2.0 μm or more and less than 7.5 μm. 〔twenty one〕 Volume cumulative particle size D at 90% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 90 The magnetic metal powder according to any one of

[16] to

[20] , wherein the particle size is 10 μm or more and 30 μm or less. EXAMPLES

[0071] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".

[0072] Example 1 Examples 1 to 5 are examples in which fine magnetic metal particles were produced. Using the DC plasma device 1 shown in FIG. 1, fine magnetic metal particles each having a core made of Fe and a shell made of SiO 2 were produced as follows. Atomized powder (particle size 10 μm, spherical) made of FeSi alloy (Si content 6.5%) was used as the first mother powder. SiO powder (5 μm, irregular shape) was used as the second mother powder. (Amount of second mother powder used) / (Amount of first mother powder used + Amount of second mother powder used) was set to 2.5%. The mixed mother powder obtained by mixing both mother powders was supplied to the device 1. The supply amount was set to 20 g / min, and the mixed mother powder was supplied to the DC plasma torch 4 through the powder supply nozzle 6. A mixed gas of nitrogen gas and argon gas was used as the plasma gas. The flow rate of nitrogen gas was set to 4 L / min, and the flow rate of argon gas was set to 15 L / min. The plasma output was set to 14 kW. The generated plasma flame was photographed from the side where the frame width was observed to be the widest, and the image was binarized to measure the frame aspect ratio, which is the ratio of the frame length to the frame width. As a result, the frame aspect ratio was 3, and it was confirmed that the plasma flame was a laminar flow. The length of the laminar flow portion of the plasma flame was 10 cm. A quartz cylinder was used as the cylindrical body 9. The length L S The flame length L of the laminar flow part in the plasma flame P Ratio of L P / L S A plasma flame was generated so that the ratio d / D of the diameter d of the plasma flame to the inner diameter D of the cylindrical body 9 was 0.80 and 0.050. The gauge pressure in the chamber was set to -10 kPa.

[0073] Example 2 Fine magnetic metal particles were obtained in the same manner as in Example 1, except that (amount of second mother powder used) / (amount of first mother powder used+amount of second mother powder used) was set to 2.0%.

[0074] Example 3 In Example 1, fine magnetic metal particles were obtained in the same manner as in Example 1, except that (amount of second mother powder used) / (amount of first mother powder used + amount of second mother powder used) was set to 2.0% and the gauge pressure in the chamber was set to -25 kPa.

[0075] Example 4 In Example 1, atomized powder (particle size 10 μm, spherical) made of FeCrSi alloy (Cr content 4.5%, Si content 3.5%) was used as the first mother powder, (amount of second mother powder used) / (amount of first mother powder used+amount of second mother powder used) was set to 3.5%, and the gauge pressure in the chamber was set to -50 kPa. The procedure was the same as in Example 1 to obtain fine magnetic metal particles.

[0076] Example 5 Fine magnetic metal particles were obtained in the same manner as in Example 1, except that (amount of second mother powder used) / (amount of first mother powder used+amount of second mother powder used) was 0.5%.

[0077] Comparative Example 1 In Example 1, the second mother powder was not used. In addition, the cylindrical body 9 was not placed in the chamber 3 of the DC plasma device 1. The plasma flame was not in a laminar flow state. Furthermore, the gauge pressure in the chamber was set to -50 kPa. Other than these, magnetic metal particles were obtained in the same manner as in Example 1.

[0078] Comparative Example 2 This comparative example is the first mother powder used in Example 1 itself.

[0079] 〔evaluation〕 The metal particles obtained in the examples and comparative examples were subjected to the above-mentioned method. SEM50 , D 50 , D 10 , D 90 , SSA, circularity coefficient, core crystallite size, and mass increase W 600 , W 700 and W 800 Furthermore, the magnetic properties, green density and green resistance were measured by the following methods. Furthermore, the flame retardancy was evaluated by the following method. The results are shown in Table 1 below.

[0080] [Method of measuring magnetic properties] The saturation magnetization Ms and coercive force Hc, which are parameters of the magnetic properties, were measured using a vibrating sample magnetometer (VSM-5 manufactured by Toei Industry Co., Ltd.) in an external magnetic field of 10 kOe. Particles with high saturation magnetization Ms and low coercive force Hc can be said to have good soft magnetic properties and excellent magnetization characteristics.

[0081] [Method of measuring green density and green resistance] The pressed powder resistance was measured using a pressed powder resistance measurement system (Mitsubishi Chemical Analytech Co., Ltd. PD-51) and a resistivity meter (Mitsubishi Chemical Analytech Co., Ltd. MCP-T600). 5 g of metal particles (sample) were placed into a probe cylinder (Φ20 mm), and the probe unit was set on the PD-51. The resistance value when a load of 20 kN was applied by a hydraulic jack was measured using the resistivity meter. The volume resistivity (pressed powder resistance) and pressed powder density were calculated from the measured resistance value and sample thickness.

[0082] [Flame retardancy evaluation method] Ignition was examined by the small gas flame ignition test of the second-class hazardous materials test method stipulated in the Fire Service Act. Specifically, the sample was spread in a hemispherical shape on an inorganic insulation board. Using a portable simple ignition device with a flame length of 70 mm, the flame was brought into contact with the sample for 10 seconds. If the combustion did not continue, this operation was repeated 10 times. Among the samples that ignited even once and continued to burn with flame or smokeless after the flame was removed, those that ignited within 3 seconds were judged to be ignitable, those that ignited within more than 3 seconds but within 10 seconds were judged to be ignitable, and those that did not ignite in any of the 10 tests were judged to be non-hazardous. In this evaluation, those that ignited within 10 seconds were rated as flammable, and those that did not ignite within 10 seconds were rated as non-flammable. The more non-flammable a sample is, the higher its heat resistance can be evaluated.

[0083] [Table 1]

[0084] As is clear from the results shown in Table 1, the metal particles obtained in each Example have a lower coercive force than the metal particles obtained in Comparative Example 1, and are superior in magnetization characteristics. In addition, the metal particles obtained in each Example had a D 50 / SSA and D50 The small diameter and high green density indicate that the powder has excellent packing properties. Furthermore, it is clear that the metal particles obtained in each Example have a smaller mass increase and higher heat resistance than the metal particles in each Comparative Example, and also have higher pressed powder resistance and better insulation properties.

[0085] Example 6 Examples 6 to 8 are examples in which coarse magnetic metal particles were produced. In Example 1, the plasma output was set to 9.8 kW, and the chamber pressure was set to -50 kPa. In addition, the cylindrical body 9 was not installed in the chamber 3 of the DC plasma device 1. Other than these, the same procedure as in Example 1 was followed to obtain coarse magnetic metal particles.

[0086] Example 7 Coarse magnetic metal particles were obtained in the same manner as in Example 6, except that (amount of second mother powder used) / (amount of first mother powder used+amount of second mother powder used) was set to 3.0%.

[0087] Example 8 In Example 6, (amount of second mother powder used) / (amount of first mother powder used+amount of second mother powder used) was set to 2.0%, and the chamber pressure was set to -10 kPa. Also, a cylindrical body 9 was placed in the chamber 3 of the DC plasma device 1. Other than these, coarse magnetic metal particles were obtained in the same manner as in Example 6.

[0088] 〔evaluation〕 For each of the coarse magnetic metal particles of the examples, the same measurements and evaluations were carried out as in Example 1. The results are shown in Table 2 below.

[0089] [Table 2] [Explanation of symbols]

[0090] 1 DC plasma device 2 Powder feeding device 3. Chamber 4 DC Plasma Torch 5. Collection Pot 6 Powder supply nozzle 7 Gas supply equipment 8. Pressure Regulating Device 9 Cylindrical body

Claims

1. A magnetic metal powder containing a magnetic metal element, the mass increase when the temperature is increased from 25° C. to 600° C. at a rate of 10° C. / min under an air flow of 150 mL / min is 6.0% by mass or less; BET specific surface area SSA (m 2 / g) at 50% cumulative volume by a laser diffraction scattering particle size distribution measurement method 50 D is the ratio of (μm) 50 A magnetic metal powder having a / SSA value of 0.010 or more and 1.0 or less.

2. Volume cumulative particle size D at 50% cumulative volume as observed by scanning electron microscope SEM50 (μm) to the volume cumulative particle diameter D 50 D is the ratio of (μm) 50 / D SEM50 The magnetic metal powder according to claim 1, wherein the Mn content is 1.0 or more and 2.8 or less.

3. The volume cumulative particle size D 50 The magnetic metal powder according to claim 1, wherein the particle size is 0.30 μm or more and 1.1 μm or less.

4. The BET specific surface area SSA is 1.5 m 2 / g or more 5.0m 2 The magnetic metal powder according to claim 1, wherein the magnetic metal powder has a molecular weight of 1000 or less.

5. Volume cumulative particle size D at 10% cumulative volume measured by a laser diffraction scattering particle size distribution measurement method 10 But, D 50 2. The magnetic metal powder according to claim 1, having a particle size of 0.15 μm or more and 0.35 μm or less, with the proviso that the particle size is smaller than 0.25 μm.

6. Volume cumulative particle size D at 90% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 90 But, D 50 2. The magnetic metal powder according to claim 1, having a particle size of 1.0 μm or more and 5.0 μm or less, with the proviso that the particle size is greater than 1.0 μm.

7. Alumina or silica is present on the outermost surface, The powder resistance when compressed with 20 kN is 1.0 x 10 7 The magnetic metal powder according to claim 1, having a resistivity of Ω·cm or more.

8. 2. The magnetic metal powder according to claim 1, comprising at least one magnetic metal element selected from the group consisting of iron (Fe), cobalt (Co) and nickel (Ni).

9. 2. The magnetic metal powder of claim 1 comprising FeSi or FeSiCr.

10. A magnetic paste comprising the magnetic metal powder according to any one of claims 1 to 9.

11. A dust core comprising the magnetic metal powder according to any one of claims 1 to 9.

12. An inductor comprising the magnetic metal powder according to any one of claims 1 to 9.

13. A method for producing a magnetic metal powder, comprising the steps of supplying a first mother powder containing a magnetic metal element into a plasma flame in a laminar flow state generated in a chamber, gasifying the mother powder in the plasma flame, and cooling the gasified mother powder to generate magnetic metal particles, A method for producing magnetic metal powder, in which the laminar flow state of the plasma flame is maintained at a depth of 1.0 cm or more and 20 cm or less.

14. The plasma flame is generated within a cylindrical body installed in the chamber; 14. The manufacturing method according to claim 13, wherein a laminar flow state of the plasma flame is maintained while maintaining a value of d / D of 0.003 or more and 0.20 or less, where D (mm) is an inner diameter of the cylindrical body and d (mm) is a maximum diameter of the plasma flame.

15. 15. The manufacturing method according to claim 13 or 14, further comprising the steps of: supplying a second mother powder made of alumina or silica together with a first mother powder into the plasma flame; gasifying both mother powders in the plasma flame; and cooling both gasified mother powders to produce magnetic metal particles having a core portion containing the magnetic metal element and a shell portion disposed on the surface of the core portion and containing an oxide of aluminum or silicon.

16. A magnetic metal powder containing a magnetic metal element, the mass increase when the temperature is increased from 25° C. to 600° C. at a rate of 10° C. / min under an air flow of 150 mL / min is 1.5% by mass or less; BET specific surface area SSA (m 2 / g) at 50% cumulative volume by a laser diffraction scattering particle size distribution measurement method 50 D is the ratio of (μm) 50 A magnetic metal powder having an SSA value of 10 or more and 100 or less.

17. Volume cumulative particle size D at 50% cumulative volume as observed by scanning electron microscope SEM50 (μm) to the volume cumulative particle diameter D 50 D is the ratio of (μm) 50 / D SEM50 The magnetic metal powder according to claim 16, wherein is 1.0 or more and 2.5 or less.

18. The volume cumulative particle size D 50 The magnetic metal powder according to claim 16, wherein the particle size is 5.0 μm or more and less than 18 μm.

19. The BET specific surface area SSA is 0.10 m 2 / g or more 0.50m 2 The magnetic metal powder according to claim 16, wherein the Mn content is 0.01 to 0.15g. 【Request 20】 Volume cumulative particle size D at 10% cumulative volume measured by a laser diffraction scattering particle size distribution measurement method 10 The magnetic metal powder according to claim 16, wherein the particle size is 2.0 μm or more and less than 7.5 μm.

21. Volume cumulative particle size D at 90% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 90 The magnetic metal powder according to claim 16, wherein the particle size is 10 μm or more and 30 μm or less.

Citation Information

Patent Citations

  • Silicon oxide-coated iron powder, method for producing the same, and molded product for inductor and inductor each using the same

    JP2019123933A

  • Silicon oxide-coated soft magnetic powder and method for producing the same

    JP2019143241A

  • Metal particle, and magnetic material paste, dust core, and inductor using the same, and method for producing the same

    JP2021175827A